Benchmarking of Gas‐Assisted Atomization Systems for Liquid Disintegration. Issue 4 (29th February 2016) - Günther, Astrid; Lampa, Aljoscha; Fritsching, Udo; Schröder, Jewe; Kleinhans, Agnes; Gaukel, Volker; Schuchmann, Heike P.; Loth, Jan‐Martin; Petermann, Marcus; Wirth, Karl‐Ernst
Abstract: Four different gas‐assisted atomizer systems are compared to assess their atomization performance for water and polymer solution feeds. An external mixing twin‐fluid atomizer serving as standard atomization configuration is compared to three rather unconventional atomization techniques. An internal mixing atomization system is represented by an effervescent atomizer that can be operated at lower air‐to‐liquid ratio than the conventional gas atomizers. Superheated atomization is an innovative technique to enhance the atomization of liquids by a phase change within the emerging spray. CO2 ‐assisted atomization takes the same line by releasing a liquid saturated with CO2 into a lower pressure environment. The atomization configurations were used to disintegrate the model fluid water and more challenging polymer solutions with higher viscosities. Resulting spray configurations and drop sizes distributions were compared. Abstract : The generation of small droplets by atomization of viscous liquids is still a challenge. To encounter the issues of lowered aerodynamic interactions and dampened instability growth, different spraying methods were used. For conventional spraying external atomization was applied and compared to the performance of effervescent atomization, CO2 ‐assisted spraying, and superheated atomization.